Interior design visual presentation a guide to graphics, models, and presentation methods - Mitton, Maureen (Hoboken, New Jersey Wiley, 2018)
"A NEWLY UPDATED AND COMPREHENSIVE GUIDE TO ALL ASPECTS OF VISUAL DESIGN

From doing a quick sketch to producing a fully rendered model, the ability to create visual representations of designs is a critical skill for every designer. Interior Design Visual Presentation, Fifth Edition offers thorough coverage of interior design communication used throughout the design process, complete with a broad range of real-world examples.

This fully updated handbook presents a full range of styles and techniques used for interior design visual communication, from hand drawing to 3D computer modeling. Its accessible, how-to approach guides you through a variety of methods for executing creative and successful design graphics, models, and presentations. Recognizing the ongoing proliferation of digital tools for visual representation, this Fifth Edition provides the latest information on software used in presentation such as Photoshop and SketchUp, and covers the integration of Revit and AutoCAD generated content into design presentations.

Covers all aspects of visual design and presentation for interior designers
Includes color illustrations that feature a wide range of project types, including residential, health care, and public projects, designed to highlight step-by-step instructions
Discusses the incorporation of 3D digital models into presentations, including use in virtual reality, and expanded information on scale models, including a discussion of 3D printing
Includes a companion website for instructors, featuring PowerPoint lecture slides and an instructor's manual

From traditional to cutting-edge techniques, Interior Design Visual Presentation, Fifth Edition gives students and professionals alike the tools to give life to their design vision."--
1 An Introduction to Drawing for Interior Design 1--
2 The Design Process and Related Graphics 29--
3 Paraline and Perspective Drawings 63--
4 Drawing and Sketching Interior Environments 81--
5 Rendering by Hand 103--
6 SketchUp and Digital Modeling 143--
7 Digital Rendering 175--
8 Scale ModelS: Physical and Digital 209--
9 Presenting Materials and Finishes 239--
10 Making the Complete Presentation 263--
Includes bibliographical references and index
Keywords: Interior decoration rendering; Interior decoration -- Design